CRYOPRESERVATION OF PRIMARY SPLENOCYTES FROM ANTIBODY PRODUCED MICE AGAINST Bitis arientans SNAKE VENOM - Ibrahim Abubakar, Isah; Ibrahim, M. H.; Gwarzo, Muhammad Y.; Kurfi, Binta G. (FUDMA JOURNAL OF SCIENCES, 2023)
Bitis Arientans are associated with the highest number of morbidity and mortality in Nigeria.The most effective treatments against snakebite is the administration of antivenom.Antibodies that is specific for a single epitope of an antigen are obtain by isolating antibody-secreting lymphocytes. These lymphocytes are found within the Splenocytes cells which can be used for a wide variety of immunology-based applications. However, development of hybridoma cell is rare and time consuming. Therefore, valuable time and cell materials can be saved through cryopreservation. This research aimed at Cryopreservation of primary splenocytes from Antibody produced mice against Bitis arientans snake venom. The LD50 of Bitis Arientans venom toxicity was determined in mice according to World Health Organization guidelines. Antibody production was achieved using six mice after immunization for six weeks and antibody titer were determined by indirect ELISA method. Myeloma cells line X63 Ag8.653 were cultured and Mouse Splenocytes with the highest immune response were removed aseptically by mechanical method and cells viability was determined then the isolated splenocytes were cryopreserved in cryovial tube stored at -80C.The LD50 was found to be 1.8mg/kg and Elisa analysis showed mice 2 and 6 to elicited highest immune response with IgG Concentration 3.1µg/ml and 4.6µg/ml. isolated splenocytes were counted to be 6.5x10 and 1.2x10 cells for mice 2 and 6 and myeloma cells to be 1.95x105 cells.In this finding antibody against Bitis Arientans venom were produced and mouse splenocytes were isolated and cryopreserved. Thus, cryopreserved splenocytes and myeloma can be used for the generation of monoclonal antibody